IMPLEMENTASI VARIABLE COSTING METHOD PADA SISTEM INFORMASI AKUNTANSI PENENTUAN HPP PADA UMKM KERIPIK TEMPE DESA LEBO - Munifah; Ahmad Ashifuddin Aqham; Eko Siswanto; Indah Dwi Astutik (Universitas Sains dan Teknologi Komputer, 2023)
Cost of goods manufactured (COGM) is an important component of making a product, because knowing the COGM of a product can be used as a reference to determine the profit margin of a product. Without knowing the COGM of a product, we will be confused in determining the selling price. The COGM calculation is very influential for the sale of a product whether the product is experiencing a profit or loss. This study aims to determine the COGM calculations that have been carried out by MSMEs are in accordance with COGM accounting calculations or are still only limited to manual calculations. In addition, the main objective of this study is to design an accounting system for determining COGM in the Tempe Chips Industry in determining the cost of production and to apply a variable costing method to determine the cost of goods manufactured in SMEs so that the correct cost of production can be presented. The results of this study indicate that based on Cost of goods manufactured calculations carried out by MSME actors it is still very low so it is necessary to revamp the HPP calculations in accordance with accounting standards. Based on the evaluation of the old system, the author wishes to offer a new system, namely the Information System for Determining the Cost of Production of Tempe Chips SMEs which is expected to be an alternative in solving problems that are being faced by business owners. This new system makes it easy for users related to the process of recording data into the database, so that related parties can easily operate.